Penerapan Akupresure pada Penyakit Hipertensi di Kelurahan Cipageran : Penelitian - Wisnusakti, Khrisna; Wulandari, Sri; Suharjiman, Suharjiman; Hidayat, Monna Maharani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Hypertension is a non-communicable disease with high prevalence and a major risk factor for cardiovascular diseases. Hypertension management requires a comprehensive approach that includes not only pharmacological therapy but also community-applicable non-pharmacological interventions. One complementary therapy that may support blood pressure control is acupressure. This community service activity aimed to improve community knowledge and skills and to support blood pressure control among patients with hypertension through the application of acupressure in Cipageran Village. The methods included health education, acupressure training and demonstration, and evaluation of blood pressure before and after acupressure application. A total of 35 participants consisting of hypertensive patients and health cadres were involved. The results showed increased participant knowledge regarding hypertension and acupressure, as well as a decrease in mean systolic and diastolic blood pressure after acupressure application. Participants also reported feeling more relaxed and experiencing reduced symptoms such as headaches. Acupressure may serve as a safe, low-cost, and easily applicable complementary therapy to support community-based hypertension management.